B0‐informed variable density trajectory design for enhanced correction of off‐resonance effects in parallel transmission. Issue 4 (28th May 2013) - Schneider, Rainer; Ritter, Dieter; Haueisen, Jens; Pfeuffer, Josef
<x xml:space="preserve">Abstract</x> Purpose To improve B1 and B0 inhomogeneity mitigation performance of spatially selective radio‐frequency (RF) pulses in parallel transmission while decreasing RF pulse power. Further enhancement of off‐resonance correction for rectilinear spoke‐trajectory‐based RF pulses with known residual geometric distortions after optimization. Methods The appropriate definition of the target magnetization pattern is discussed regarding the maximum physical excitation resolution. Furthermore, a novel variable‐density trajectory design is introduced, which subsamples accrued B0 phase error elevations in k‐space. A simulation study (echo‐planar and spiral 2DRF) at different off‐resonance levels and pulse acceleration factors was pursued using data from a whole‐body 2‐channel parallel transmit 3T MRI system. The new trajectory design for echo‐planar 2DRF was validated in human in‐vivo experiments. Results Proper target pattern definition can require spatial filtering, such that RF pulse optimization is prevented from lower excitation performance with significant higher RF power level. The new trajectory design proposed can considerably improve off‐resonance compensation, while further reducing the RF power, e.g., 43% less RMSE with 79% less RF power for spoke based pulses. Conclusion The proposed methods offer significant improvements of the excitation performance (homogeneity and acceleration), while significantly decreasing the RF power. Furthermore, single‐channel transmit RF pulse performance can be similarly improved. Magn Reson Med 71:1381–1393, 2014. © 2013 Wiley Periodicals, Inc.